Improved Implementation of Hybrid Approach in Cloud Environment - Rao, G. Srinivasa; Anuradha, T (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a technological advancement which is based on the concept of dynamic resources provisioning using internet. Web 2.0 technologies play a central role. Hybrid approach to load balancing will provides better results in providing the improvement in the load balancing. Combination of Round robin with Throttled Algorithm in a combination RTH is observed with some disadvantages such as updating the Index table leads to an overhead and sometimes it is causing delay in providing response to arrived requests. It is found a slight improvement in combination with RTH and ESCE in hybrid approach manner to called RTEH.RTEH Algorithm also shown drawback as it is still getting overhead in updating the index table. Then Artificial Bee Colony Optimization technique is combined with RTEH and obtained RTEAH Algorithm has shown betterment in case of some load balancing parameters such as response time, Execution time etc